«Siberian Satrap» M. M. Lashevich and his death in Harbin - M. V. Krotova (Омский научный вестник: Серия "Общество. История. Современность")
The article is dedicated to the Soviet politician M. M. Lashevich (1884–1928), a participant in the revolution and the Civil War, chairman of the Siberian Revolutionary Committee. The relevance of the study is due to the fact that his activities as a fellow chairman of the Board of the CER in 1926–1928 little known, as are the causes of death in Harbin. The purpose of the article is to reconstruct the final period of Lashevich’s life in the context of the Soviet presence in China, with emphasis placed on the perception of Lashevich’s personality by Russian emigration in Manchuria, the circumstances of his death and posthumous biography using an anthropological approach and the biographical method. The research is based on unpublished sources, ego-documents and periodical materials from Harbin. The author emphasizes that the study of such extraordinary figures as Lashevich is important not only for understanding Soviet policy in China, but also for clarifying the problems of perception and assessment of the activities of Soviet leaders by ideological opponents.